Rice Sustainability Trend: A bibliometric review - Adonir Venuzino Rocha Both; Saraiva, M.; Manuel Luis Tibério (Research, Society and Development, 2021)
Sustainability isa topic of interest to science and organizations, an emerging research area in the agrifood field and business management. This area aims to investigate the processes that lead organizations to sustainability and those that lead to organizational learningand the consequent continuous improvement. This work seeks to understand the evolution and trend of studies on the sustainability of the rice value chain. In this sense, a bibliometric review of the literature in the Scopus database was carried out as a methodological procedure, in the years 2001 to 2021, to observe the publications on the theme of sustainability of the rice value chain existing over the 20 years of this century. Among the results obtained, it was verified that the publications on the topic addressed had an exponential growth from the year 2015, that is, from 80 publications to more than 400 in 2019, and it can be observed that this theme has become of due importance, with a view to sustainability. As an essential result of this study, it is observed that in 2019 there were more than 200 publications on the theme of rice sustainability. All of this leads to the belief that there is an interest on the part of researchers and authors to deepen their research questions in this area, with different approaches to understand the value chain and the sustainability of rice